2008
DOI: 10.1007/s11105-008-0076-x
|View full text |Cite
|
Sign up to set email alerts
|

UVH6, a Plant Homolog of the Human/Yeast TFIIH Transcription Factor Subunit XPD/RAD3, Regulates Cold-stress Genes in Arabidopsis thaliana

Abstract: The UVH6 gene from Arabidopsis thaliana is predicted to function in transcription regulation, based on known activities of its human and yeast homologs. In this study, we show that uvh6-1 mutants are ultra-sensitive to cold and suggest that this defect results from reduced expression of cold-stress genes. Comparison of mRNA levels in cold-treated wild-type and uvh6-1 plants reveals that expression of two cold-stress genes (Cor6.6 and Cor15a) is impaired in the mutant. In contrast, the mutant shows normal cold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…As a component of TFIIH, XPD/UVH6 plays an important role in transcription. uvh6 mutants have been reported to exhibit aberrant levels of several RNAs and proteins ( Jenkins et al 1997 ; Liu et al 2008 ; Hall et al 2009 ). With respect to its role in heat tolerance, uvh6 was reported to contain increased levels of HSP21 ( Jenkins et al 1997 ) but normal levels of HSP101 and sHSPs ( Larkindale et al 2005 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a component of TFIIH, XPD/UVH6 plays an important role in transcription. uvh6 mutants have been reported to exhibit aberrant levels of several RNAs and proteins ( Jenkins et al 1997 ; Liu et al 2008 ; Hall et al 2009 ). With respect to its role in heat tolerance, uvh6 was reported to contain increased levels of HSP21 ( Jenkins et al 1997 ) but normal levels of HSP101 and sHSPs ( Larkindale et al 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Liu et al (2008) show that heat treatment reduced levels of AtKu70 and AtKu80 transcript in wild type, but this down-regulation did not occur in uvh6 . In response to another stress, cold, Hall et al (2009) found that uvh6 mutants failed to induce some cold stress genes but not all. Thus the uvh6-1 mutant appears to exhibit abnormal regulation of a subset of genes rather than global defects in transcription ( Hall et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hall et al . () found that uvh6 ‐ 1 mutants are sensitive to cold stress, and abnormally regulate a subset of cold stress‐responsive genes during transcription. Thus, UVH6 in Arabidopsis may function as a transcriptional regulator that induces the gene expression required to facilitate HS tolerance.…”
Section: Discussionmentioning
confidence: 99%